Towards energy efficient NB-IoT: A survey on evaluating its suitability for smart applications. (2022) - Singh Bali, Malvinder; Gupta, Kamali; Kour Bali, Kanwalpreet; Singh, Pramod K.
Abstract: With the Advancement of Technology, IoT has gained momentum by providing Machine to Machine (M2M) Communication bringing smart devices closer to the proximity of end users. Although IoT is expected to bring together 75.4 billion of devices by 2025, improving the quality of life beyond expectations, but we will have to pay a bigger price for all this in the form of expatiated energy consumption and carbon footprints. These Constraints have motivated researchers to put forward a solution for energy efficient green communication. However, the increasing number of devices annually is also a matter of concern. To deal with such an invidious situation, we have brought together two magnanimous technologies- NB-IoT and Green IoT. The concept of Green IoT has been of paramount importance as it addresses a very important IoT challenge by restricting energy usage of IoT devices and bringing forwards new tactics to deal with it. LPWA technology has come to the rescue, by connecting numerous devices over a wide domain with optimized battery life, utilizing very less power for connectivity and hence curbing the cost to a great extent. Various LPWA technologies like LoRA, Zigbee, Sigfox etc offer prominent solutions to the users by reducing Carbon emissions and making efficient Utilization of power resources but to provide a maximum global outreach of devices to the users and avoid Infrastructure cost, 3GPP in Release-13 provided a cellular based Licensed Technology called NB-IoT. This Technology provides features which can bring maximum benefits to LPWA technology in Market like Low power Consumption, massive connection to IoT devices and enhanced Indoor Coverage. In our research paper, we have highlighted the NB-IoT Technology, its technical features and applications. We have also made an effort in proposing a green NB-IoT model for Smart agriculture as an initiative to promote use of green IoT features and applications. Also Proposed NB-IoT model for Smart agriculture towards green IoT.